Gas6/TAM system as potential biomarker for multiple sclerosis prognosis - D’Onghia, Davide; Colangelo, Donato; Bellan, Mattia; Tonello, Stelvio; Puricelli, Chiara; Virgilio, Eleonora; Apostolo, Daria; Minisini, Rosalba; Ferreira, Luciana L.; Sozzi, Leonardo; Vincenzi, Federica; Cantello, Roberto; et al. (Frontiers in Immunology, 2024)
Introduction. The protein growth arrest specific 6 (Gas6) and its tyrosine kinase receptors Tyro-3, Axl, Mer (TAMs) are ubiquitous proteins involved in regulating inflammation, and apoptotic bodies clearance. Multiple sclerosis (MS) is the most common inflammatory demyelinating disease of the central nervous system, leading to progressive and irreversible disability if not diagnosed and treated promptly. Gas6 and TAMs have been associated with neuronal remyelination and stimulation of oligodendrocyte survival. However, few data are available regarding clinical correlation in MS patients. We aimed to evaluate soluble levels of these molecules in cerebrospinal fluid (CSF) and serum at MS diagnosis and to correlate them with short-term disease severity. Methods. In a prospective cohort study, we enrolled 64 patients with a diagnosis of Clinical Isolated Syndrome (CIS), Radiological Isolated Syndrome (RIS) or Relapsing-Remitting (RR) MS, according to McDonald 2017 Criteria. Before any treatment initiation, we sampled serum and CSF, and collected clinical data: disease course, presence of gadolinium-enhancing lesions and expanded disability status score (EDSS). At last clinical follow up we assessed EDSS, and calculated MS severity score (MSSS) and Age-Related MS severity (ARMSS). Gas6 and TAMs were determined with ELISA kit (R&D Systems) and compared to neurofilaments (NFL) levels evaluated with SimplePlexTM fluorescencebased immunoassay. Results. At diagnosis, serum sAxl was higher in patients receiving none or lowefficacy disease-modifying treatments (DMTs) versus patients with high-efficacy DMTs (p = 0.04). Higher CSF Gas6 and serum AXL were associated with an EDSS ≤ 3 at diagnosis (p = 0.04; p = 0.037). Serum Gas6 correlates to a lower MSSS (r2 = -0.32, p = 0.01). Serum and CSF NFLs were confirmed as disability biomarkers in our cohort, according to EDSS (p = 0.005; p = 0.002) and MSSS (r2 = 0.27, p = 0.03; r2 = 0.39, p = 0.001). Results were corroborated by multivariate analysis. Conclusions. Our data suggest a protective role of Gas6 and its receptor in patients with MS and suitable severity disease biomarkers.